Patient Perceptions of Generalist Therapy for Schizophrenia with Violent Risk: A Phenomenological Study in Indonesia - Permana, Hendrian Hadi; Aiyub; Jannah, Syarifah Rauzatul (Queeva Publishing, 2025)
Background: Generalist Therapy (GT) is a nursing approach that integrates physical, psychological, social, and spiritual care tailored to individual needs. While commonly used in mental health nursing, its implementation varies across countries. In Indonesia, GT is delivered through culturally adapted implementation strategies. These include deep breathing exercises, pillow-punching, medication adherence, assertive verbal communication, and spiritual practices. Although GT has become a standard practice in Indonesian mental health services particularly in Aceh Province, research on patient perceptions, especially among those with schizophrenia and a history of violence, remains limited. This study aims to explore patients’ subjective experiences of GT. Methods: This qualitative study employed a phenomenological approach. Data were collected through in-depth interviews with ten patients diagnosed with schizophrenia. The interviews were analyzed using Colaizzi’s seven-step method. Results: Three major themes emerged from the data: (1) the effectiveness of GT in emotional regulation, including managing anger, promoting calmness, and the role of medication in reducing negative emotions; (2) resilience enhancement, encompassing positive meaning-making, therapy commitment, improved social functioning, and self-control; and (3) barriers to GT implementation, including internal (emotional issues, low insight, restrictive personal beliefs, cognitive decline, and low participation) and external obstacles (limited facilities and overcrowded wards). Conclusion: GT is perceived as helpful in emotional regulation and recovery support. It strengthens resilience and improves patient insight, especially when supported by a conducive environment. Incorporating patients’ perspectives into therapeutic planning may enhance the effectiveness of mental health care.